Determinan Migrasi Pekerja Migran Indonesia (PMI) ke Luar Negeri di Jawa Timur - Eva Sulivatun Durriah (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of economic factors on the migration of Indonesian Migrant Workers (PMI) from East Java Province to overseas. The independent variables studied include minimum wages, population density, and poverty levels, with the number of PMI as the dependent variable. This study uses a quantitative method with a panel data regression approach to secondary data from seven cities/regencies in East Java during the period 2018–2022. The best multiple linear regression model analysis method uses the Random Effect Model (REM). The results of the study indicate that the minimum wage variable has a negative and insignificant effect on Indonesian Migrant Worker Migration. Meanwhile, population density and poverty levels have a positive and significant effect on PMI Migration.
Approved by Teddy
Keywords: Minimum Wage; Indonesian Migrant Workers; Population Density; Poverty